Team Achievement Division Student Learning Model using Mind Mapping to Improve Learning Activities in the Learning Management of Management System in Vocational School - Didit Agung Prasojo; Cicilia Dyah Sulistyaningrum Indrawati; Jumiyanto Widodo (Universitas Sebelas Maret, 2019)
the purpose of this study was to improve the learning of students of class XI Office Administration of Vocational High School 1 Sukoharjo in learning the subjects of the 2016/2017 lesson archive system through the application of the cooperative learning model of the Division Student Achievement Team (STAD Method) using the Mind Maping learning method. This type of research conducted by researchers is Classroom Action Research (CAR). The subjects of this study were students of class XI AP of SMK Negeri 1 Sukoharjo in the 2016/2017 academic year which were debated by 36 people. The results showed active students during the pre-cycle had not reached 75%. In cycle 1 activity increased in visual aspect activity 61.11%, oral activity 55.56%, drawing activity 75%, mental activity 69.44% and emotional activity 75%. Furthermore, in cycle 2 the activity increased significantly in the aspect of visual activity 94.44%, oral activity 91.67%, drawing activity 94.44%, mental activity 94.44% and emotional activity 97.00%.